2022
DOI: 10.1021/acs.jpcc.2c02803
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Activity Trends for the Electrochemical Production of H2O2 on M–N–C Single-Atom Catalysts Using Theoretical Kinetic Computations

Abstract: Metal−nitrogen−carbon (M−N−C) single-atom catalysts (SACs) have shown high potential to generate H 2 O 2 through the two-electron oxygen reduction reaction (2e − ORR) pathway in an acidic electrolyte. However, there is still a lack of effective kinetic computation to reveal M−N−C SACs' intrinsic catalytical performance toward 2e − ORR. Here, we combine the experimental and computational efforts to study the 2e − ORR activity trends of M−N−C SACs (M = Co, Fe, and Mn). The experimental results show that Co−N−C a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 55 publications
0
13
0
Order By: Relevance
“…Currently, researchers are devoted to noble metal minimization [69][70][71]. Constructing atomically dispersed catalysts has received extensive attention, which could lower the cost and realize end-on adsorption [72][73][74]. These factors, such as ligand effect, support effect, and impact of metal loading has an evident influence on the ORR activity and selectivity.…”
Section: Atomically Dispersionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, researchers are devoted to noble metal minimization [69][70][71]. Constructing atomically dispersed catalysts has received extensive attention, which could lower the cost and realize end-on adsorption [72][73][74]. These factors, such as ligand effect, support effect, and impact of metal loading has an evident influence on the ORR activity and selectivity.…”
Section: Atomically Dispersionmentioning
confidence: 99%
“…Inspired by this, researchers are dedicated to transitional metal-nitrogen-doped carbon (M-N-C, M = Fe, Co, Mn, Cu, Ni) materials, as a promising alternative to the conventional noble metal-based catalysts (e.g., Pd, Au, or Pt) [112,113]. M-N-C materials exhibit high activity comparable to the noble metal-based catalysts with much lower cost [74,[114][115][116][117]. Normally, their ORR activity and selectivity are affected by the central metal atoms, coordination heteroatoms, and other environmental atoms.…”
Section: Atomically Dispersed Transition Metal Catalystsmentioning
confidence: 99%
“…The difference in the desorption energy between H 2 O* and HOOH* intermediates on the active center is an important descriptor to predict the H 2 O 2 selectivity of catalysts. 76 Penta-coordinated Co-N-C conguration (O-Co-N 2 C 2 ) with the Co center coordinated by two N atoms, two C atoms, and one O atom was conrmed to slightly increase the charge state of the Co center, which can facilitate the adsorption energy towards *OOH to enable the 2e − ORR. In a neutral solution, the as-synthesized O-Co-N 2 C 2 exhibited a selectivity of over 90% in the potential range from 0.36 to 0.8 V vs. RHE.…”
Section: Metal-based Materials For 2e − Orr Catalysismentioning
confidence: 99%
“…The difference in the desorption energy between H 2 O* and HOOH* intermediates on the active center is an important descriptor to predict the H 2 O 2 selectivity of catalysts. 76…”
Section: Selectivity During the Cathodic Reduction Processmentioning
confidence: 99%
“…M-N-C materials can bring down the cost and maximize the utilization efficiency simultaneously. Based on the computer technologies and experimental methods, it was shown that Co-N-C follows a 2e − ORR pathway to H 2 O 2 with a proper adsorption energy of * OOH [35][36][37][38]. Therefore, carbon materials can be used in acidic media for H 2 O 2 electrosynthesis via structure geometric regulation, heteroatom doping, and transition metal introduction.…”
Section: Introductionmentioning
confidence: 99%